Occupational skin cancer induced by ultraviolet radiation and its prevention - Diepgen, Thomas L.; Fartasch, Manigé; Drexler, Hans (British journal of dermatology, 2012)
Skin cancer is by far the most common kind of cancer diagnosed in many western countries and ultraviolet radiation is the most important risk factor for cutaneous squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). Although employees at several workplaces are exposed to increased levels of UV radiation, skin cancer due to long-term intense occupational exposure to UV radiation is often not considered as occupational disease. The actually available evidence in the epidemiological literature clearly indicates that occupational UV radiation exposure is a substantial and robust risk factor for the development of cutaneous SCC and also clearly shows a significant risk for developing BCC. There is enough scientific evidence that outdoor workers have an increased risk of developing work-related occupational skin cancer due to natural UV radiation exposure and adequate prevention strategies must be implemented. The three measures which are successful and of particular importance in the prevention of nonmelanoma skin cancer in outdoor workers are changes in behaviour regarding awareness of health and disease resulting from exposure to natural UV radiation, protection from direct UV radiation by wearing suitable clothing, and regular and correct use of appropriate sunscreens.